Efficacy and safety of Cortex Eucommiae (Eucommia ulmoides Oliver) extract in subjects with mild osteoarthritis: Study protocol for a 12-week, multicenter, randomized, double-blind, placebo-controlled trial - Ahn, Hyeon Yeong; Cho, Jae-Heung; Nam, Dongwoo; Kim, Eun-Jung; Ha, In-Hyuk (Medicine (Baltimore), 2019)
Osteoarthritis (OA) is a major degenerative disease that affects the elderly. The global prevalence of OA is increasing annually. However, current treatments are unable to halt the progress of OA. At present, pharmacological treatments such as non-steroidal anti-inflammatory drugs (NSAIDs) and cyclooxygenase-2 (COX-2) inhibitors control the pain; however, there may be side effects to these medications. We hypothesized that Cortex Eucommiae (CE; Eucommia ulmoides Oliver) extract, which is used as a dietary supplement, may slow down or prevent OA. This is a protocol for a 12-week, multicenter, randomized, double-blind, placebo-controlled, parallel-group study to evaluate the efficacy and safety of CE extract in subjects with mild OA. One-hundred subjects with mild OA will be recruited and randomly divided in a 1:1 ratio into 2 groups. One group will receive CE extract for 12 weeks and the other group will receive placebo for 12 weeks. Outcomes will be evaluated by using the visual analog scale (VAS), Korean-Western Ontario and McMaster Universities index (K-WOMAC), Korean-Short Form health survey-36 score (KSF-36), and laboratory test results. This clinical trial is expected to provide evidence of the efficacy and safety of CE extract as a treatment for mild OA. Clinical Trials.gov NCT03744611, registered on November 12, 2018, at https://clinicaltrials.gov/ct2/show/NCT03744611.